The majority of type 2 diabetic patients in Finnish primary care are at very high risk of cardiovascular events: A cross-sectional chart review study (STONE HF) - Metsärinne, Kaj (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2022)
• Over 60% of primary care T2D patients were at very high risk of cardiovascular events. • DKD was underdiagnosed even when eGFR and albuminuria were measured. • Routine screening of albuminuria and systematic diagnosis of HF require more focus. • The use of treatments with proven cardioprotective effects is currently suboptimal.